Representing Wealth in a Changing Pastoral Economy: A Comparison of Traditional and New Metrics in Maasailand, Kenya. (1st January 2016) - BurnSilver, Shauna
Abstract : East African pastoralism faces complex challenges. Responses include diversification and intensification strategies. Herd size as a measure of pastoral 'wealth' is hypothesised as insufficient to reflect emergent patterns of wellbeing. Wealth distributions of Maasai households are compared across four wealth metrics - highlighting different socio-economic criteria. Using Kappa statistics, a TLU-based 'wealth' distribution is compared to measures of: 1) qualitative wealth; 2) improved-breed TLUs; and 3) diversified wealth. Livestock remain important within this system. Trajectories of diversification and intensification for wealthy versus poor pastoral households emerged. Mixed methods for assessing wealth are necessary to understand livelihood changes and better target development.